SHEEHAN SYNDROME PRESENTING WITH SEVERE HYPONATREMIA: A CASE REPORT - Gia Bao, Tran; Nhu Thao, Tran; Hoang Thi An, Nguyen; Thanh Vy, Nguyen; Hoa Binh, Pham; Thi May Hong, Nguyen (Tạp chí Sức khỏe và Lão hóa, 2025)
Sheehan syndrome, characterized by pituitary necrosis secondary to postpartum hemorrhage, results in partial or complete hypopituitarism. Diagnosis is often delayed due to its nonspecific clinical manifestations; however, the condition can lead to life-threatening complications such as hyponatremia. We present the case of a 56-year-old woman admitted with symptomatic severe chronic hyponatremia, who was subsequently diagnosed with panhypopituitarism caused by Sheehan syndrome. The patient was successfully managed with hypertonic saline infusion and hormone replacement therapy (levothyroxine and hydrocortisone). This case emphasizes the importance of obtaining a thorough obstetric history and maintaining a high index of suspicion for Sheehan syndrome in middle-aged women presenting with unexplained hyponatremia.